Lawyers, Artificial Intelligence, and Fabricated Jurisprudence: A Comparative Analysis of Legal Ethics - Ramadhan, Febriansyah; Musthafa, Annas Rasid; Taniady, Vicko (Jurnal Media Hukum, 2026)
The generative AI systems have significant implications for their use in the legal field, as they may create epistemic risks through the phenomenon of AI hallucinations, which can generate fabricated or inaccurate information. These risks are further reinforced by automation bias, which encourages excessive reliance on AI-generated outputs without adequate verification. This study aims to analyze the ethical risks and professional responsibilities associated with the use of AI by lawyers, particularly in relation to the use of fabricated jurisprudence generated by AI. This research employs a doctrinal legal research method supported by ethical, legislative, and comparative approaches. The findings indicate that the failure to verify AI-generated outputs may constitute a violation of lawyers’ ethical obligations and professional responsibilities. Therefore, this study recommends the development of a risk-based professional responsibility framework through the enactment of legislation on artificial intelligence and the revision of the advocates’ code of ethics to ensure the responsible use of technology in legal practice.